-2(c+3)=76

Simple and best practice solution for -2(c+3)=76 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(c+3)=76 equation:


-2(c+3)=76

We simplify the equation to the form, which is simple to understand
-2(c+3)=76

Reorder the terms in parentheses
+(-2c-6)=76

Remove unnecessary parentheses
-2c-6=+76

We move all terms containing c to the left and all other terms to the right.
-2c=+76+6

We simplify left and right side of the equation.
-2c=+82

We divide both sides of the equation by -2 to get c.
c=-41

See similar equations:

| 2w=5(6) | | -4.6x+1.1=21.9 | | w-5w+w+10w+w+w= | | 2-3x=40-8x-1x-10 | | 8m-10=-1+9m | | 2x=1x+15 | | 9.2x=25.76 | | 3+5+4= | | 6x-4y+y+-3x+x= | | 10-5d=7d-10 | | 12x^2-311-9th=0 | | S^2+5s+5=0 | | x+10(2x)=x+25(x) | | -6y=25 | | 3n-6-6-2n=4n-3 | | -6y=19 | | 0.75m+14=1.78m-10.3936 | | -9-2=4x+1-3x | | 2(2x+5)-3=25 | | 4x+4+x-1= | | 12*12+45+12= | | 14f+6f=4(5)square | | -8=-(-x+4) | | 5t-3=12+7t | | x-4(x-13)=26 | | -n-8=10+n | | -9-11x=69 | | 4e+8=24 | | 10k^2-27k-28=0 | | 3=5y | | 3d+6d=9square | | -6v=-8v-10 |

Equations solver categories